2004
DOI: 10.1021/jp049833s
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of Formic Acid Reaction Products on TiO2(110)

Abstract: Using chemical-state-specific scanned-energy-mode photoelectron diffraction (PhD) from O 1s and C 1s photoemission, we have determined the local structure of the surface species produced on the rutile TiO 2 (110) surface as a result of room temperature exposure to formic acid. The results show clear evidence for the coexistence of formate, HCOO, and hydroxyl, OH, surface species. The formate species is aligned along [001], bridging an adjacent pair of surface 5-fold-coordinated Ti atoms with the formate O atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
124
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(138 citation statements)
references
References 32 publications
14
124
0
Order By: Relevance
“…The magnitude and sign of near-surface layer relaxations of clean TiO 2 (110) have been studied extensively in the last few years, and a PhD study has contributed to this topic [34], but the local character of the structural information intrinsic to this technique means PhD data from an adsorbate has limited sensitivity to these parameters. We might remark, though, that the earlier study of coadsorbed formate and hydroxyl on this surface [20] showed smaller relaxations than those of the clean surface, and this may also be inferred in the present study, consistent with the behaviour of metal surfaces that adsorbates commonly reduce 13 the magnitude of any clean surface relaxation.…”
Section: General Discussion and Conclusionsupporting
confidence: 90%
See 3 more Smart Citations
“…The magnitude and sign of near-surface layer relaxations of clean TiO 2 (110) have been studied extensively in the last few years, and a PhD study has contributed to this topic [34], but the local character of the structural information intrinsic to this technique means PhD data from an adsorbate has limited sensitivity to these parameters. We might remark, though, that the earlier study of coadsorbed formate and hydroxyl on this surface [20] showed smaller relaxations than those of the clean surface, and this may also be inferred in the present study, consistent with the behaviour of metal surfaces that adsorbates commonly reduce 13 the magnitude of any clean surface relaxation.…”
Section: General Discussion and Conclusionsupporting
confidence: 90%
“…This chemical shift is essentially the same as that seen for formate on TiO 2 (110), but also for hydroxyl species on this surface [20].…”
Section: Xps Characterisationsupporting
confidence: 75%
See 2 more Smart Citations
“…[1][2][3][4] ). To date, most progress has been achieved for the simplest -COOH containing molecule, namely formic acid (HCOOH), on the prototypical rutile TiO 2 (110)(1×1) surface 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . On this substrate, it is well known that at room temperature formic acid adsorbs dissociatively, i.e.…”
Section: Introductionmentioning
confidence: 99%